Kertoacanthoma: To Excise or Not to Excise? - Gamal-AbdelNaser, Ayat (Journal of College of Medical Sciences-Nepal, 2024)
Background Although surgical excision is considered the gold standard for management of keratoacanthoma, there is lack of consensus regarding its best management options. This confusion originates due to the few number of reports describing keratoacanthoma cases. This report presents a case of keratoacanthoma that was managed using the conservative choice. A 49-year-old woman presented with a disfiguring exophytic mass at her lower lip that enlarged continuously over 3 weeks’ time. The patient had no significant medical, dental or family history or lymphadenopathy. The midline of the lower vermilion border showed a solitary soft sessile dome-shaped papule that was covered by non-keratinized mucosa with a central keratin plug at the top. The lesion was managed conservatively with favorable outcomes. The self-healing potential of the lesion provides amazing results. When signs of regression are seen, conservative approach is advised.